Investigation of varicella zoster virus glycoprotein-specific T cell responses - Malavige, G; Malavige, Gathsaurie (2007)
T cells are believed to be important in the control of varicella zoster virus (VZV) replication but little is known of T cell epitopes and the relationships between T cell responses, viral load and clinical disease during primary infection. I initially set to investigate the immune responses to two of the main VZV glycoproteins (gE and gI) using ex vivo and cultured IFNγ ELISpot assays. I identified several novel CD4+ T cell epitopes within gE and gI and characterized the phenotype of gE DRB1*1501 tetramer specific responses in healthy immune donors. I then set out to investigate the function and phenotype of VZV specific T cells in primary infection and their relationship to viral loads and clinical disease severity by using glycoprotein E/DRB1*1501 specific MHC class II tetramers, ex vivo IFNγ ELISpot assays and quantitative real time PCR assays. I compared the frequency and phenotype of specific T cells with virological and clinical outcomes in 32 adult individuals with primary VZV infection. In healthy immune donors, the gE specific T cells showed a early intermediate stage of differentiation with evidence of recent activation. Patients with acute primary infection had higher VZV/DRB1*1501 tetramer specific T cell responses and expressed markers of activation and effector differentiation. Viral loads were found to be significantly higher in patients with moderate to severe infection compared to those with mild infection (p<0.001). A significant inverse correlation was seen between the viral loads and the ex vivo IFNγ ELISpot responses of the patients (p<0.05, r=-0.64). These data would be compatible with a role for gE and gl-specific T cells in the control of viral replication during both primary infection and re-activation.